A scanning reflection X‐ray microscope for magnetic imaging in the EUV range. (13th November 2019) - Schümmer, Andreas; Mertins, H.-Ch.; Schneider, Claus Michael; Adam, Roman; Trellenkamp, Stefan; Borowski, Rene; Bürgler, Daniel Emil; Juschkin, Larissa; Berges, Ulf
Abstract : A new zone plate reflection X‐ray microscope is presented for magneto‐optical domain imaging in the EUV and X‐ray range. Abstract : The mechanical setup of a novel scanning reflection X‐ray microscope is presented. It is based on zone plate optics optimized for reflection mode in the EUV spectral range. The microscope can operate at synchrotron radiation beamlines as well as at laboratory‐based plasma light sources. In contrast to established X‐ray transmission microscopes that use thin foil samples, the new microscope design presented here allows the investigation of any type of bulk materials. Importantly, this permits the investigation of magnetic materials by employing experimental techniques based on X‐ray magnetic circular dichroism, X‐ray linear magnetic dichroism or the transversal magneto‐optical Kerr effect (T‐MOKE). The reliable functionality of the new microscope design has been demonstrated by T‐MOKE microscopy spectra of Fe/Cr‐wedge/Fe trilayer samples. The spectra were recorded at various photon energies across the Fe 3 p edge revealing the orientation of magnetic domains in the sample.